TED Talks Use in Speaking Class for Undergraduate Students - Mia Refsi Choirunnisa; Fatimah Mulya Sari (Jambura Journal of English Teaching and Literature, 2021)
ABSTRACT The media essentially supports the teaching and learning process. Video such as from TED Talks source becomes one of the teaching media that can be used by both parties, a teacher and students to improve English skill, especially for speaking skill. In this paper, the purpose is to explore the students' responses toward the implementation of TED Talks in their speaking class. The subjects were 23 undergraduate students who have experienced to watch TED Talks video for supporting their learning process. This study applied a descriptive qualitative method. To gather data, a questionnaires that were distributed through google form with close-ended questions were employed. The findings showed that most students expressed a positive response to the use of TED Talks video to support their speaking class. They assumed that the TED Talks video encouraged them to improve their speaking skill. Besides, there were some benefits to their learning process. They mentioned that they could learn about how to deliver their ideas well, how to express their critical thinking, and how to use appropriate accent, dialect, pronunciation, and fluency. Thus, the students might overcome their difficulties in understanding the speech because of the video’s powerful topics and the delivery speech from non-native speakers.